PENGARUH MOTIVASI TERHADAP KINERJA KARYAWAN (STUDI KASUS DI KOPERASI SYARIAH INTISABI UJUNG BERUNG BANDUNG) - Yasir Muharram Fauzi (Masoem University, 2019)
This research is motivated by a fundamental problem in all organizations, namely the events that occur in the field of organizational dynamics which, according to the initial hypothesis, there are problems regarding polarization and optimization of the ability to empower Human Resources, especially in terms of motivation. The task of the organization is how to manage human resources in order to carry out the tasks as expected to achieve organizational goals. Then the organization must be able to build and improve employee performance. This can be accomplished in several ways. In this case the researchers tested the effect of motivation on employee performance at the Ujung Berung Bandung Syariah Instisabi Cooperative. The purpose of this research is to find out how much influence the motivation has on employee performance at the Ujung Berung Bandung Syariah Instisabi Cooperative. This journal is expected to be useful for Instisabi Sharia Cooperatives in order to improve employee performance and as input or reference for further research.The research method used in this study is to use an associative quantitative method. The research data was obtained from primary data by distributing questionnaires and then processed using SPSS 23 applications. Researchers also obtained data from the theory of experts. This theory is used to strengthen analysis.The results showed that the motivation variable showed a significant effect on employee performance. The predictive ability of these variables on the level of employee performance in this study amounted to 0.202 or 20.2% while the remaining 79.8% was influenced by other factors not included in the study.